Bay Timoun Ou Manje - Glenda L. Warren (EDIS, 2003)
This document is FCS 1065-Hai, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: June 1997. Publication date: January 2003.  Adapted from the third edition (1995) of "Eating Right is Basic," developed by Michigan State University Extension.